Prevalence of Intestinal Parasites in Food Handlers of Bandar Abbas, Southern Iran - Mehrgan HEYDARI-HENGAMI; Yaghoob HAMEDI; Majid NAJAFI-ASL; Khojasteh SHARIFI-SARASIABI (Tehran University of Medical Sciences, 2017)
Background: Food handlers play a significant role in the dissemination and transmission of enteropathogenic microorganisms, including intestinal parasites. The aim of this study was to determine the prevalence of intestinal parasites in food handlers of Bandar Abbas, southern Iran. Methods: In this cross-sectional study, 800 stool samples were randomly collected in a period of 6 months from Jun to Nov 2015. The diagnosis was made on direct wet mount, formalin-ether concentration, Ziehl-Neelsen, and Trichrome stained slides. Results: 34.9% of participants were positive for stool parasites. The most infected individuals were seen in the workers of bakeries 54.3%, factories 41.1% fast foods 35.7%, supermarkets 34.7%, restaurants 33.9%, offices 29.8%, butchers 27.3% and coffee shops 26.7% respectively (P<0.05). The intestinal parasites were Blastocystis hominis 24.3%, Entamoeba coli 8%, Giardia lamblia 6.8% and Dientamoeba fragilis 4.3% respectively. Only two infections by Hymenolepis nana (0.3%) and one by Enterobius vermicularis (0.1%) were detected in this study. Living in the workplace and direct contact with the raw foodstuff affected the prevalence of intestinal parasites (P<0.05). Conclusion: The use of concentration methods for the detection of intestinal parasites as well as continuous and effective education in short-term courses to promote hygienic behavior is suggested.